Administration of Gemcitabine for Metastatic Adenocarcinoma during Pregnancy: A Case Report and Review of the Literature - M. Wiesweg; S. Aydin; A. Koeninger; A. Stein; U. Schara; C. van Roye; J. Hense; A. Welt; M. Schuler (American Journal of Perinatology Reports, 2014)
Abstract We present the case of a 38-year-old woman diagnosed with metastatic adenocarcinoma of the biliary tract in the 18th week of pregnancy. Chemotherapy based on cisplatin and gemcitabine was administered, reaching disease stabilization until late-preterm delivery at 35 + 0 weeks of gestation. The infant was healthy and showed no malformations. Her head circumference was small, yet no neurological and behavioral defects have been detected. Development was normal during 14 months of follow-up. We discuss the implications of metastatic cancer in pregnancy with focus on therapeutic options for metastatic adenocarcinoma of the biliary tract. In this context, available data for the active regimens in biliary tract cancers—platinum compounds and gemcitabine—are discussed. This report is the fourth in the literature detailing the application of gemcitabine during pregnancy and the first presenting longer term follow-up, complementing available evidence that gemcitabine-based regimens are feasible in this situation.